A Short Note on a Visit to the Anil Hardboards Ltd., Bombay - Sen, N. N. (Indian Forester, 1959)
The process of utilization of billets of all kinds of hardwood species at present used either as firewood or for the manufacture of charcoal or left in the forest to rot adopted by a recently established factory of Bombay in the manufacture of fibre-board is described. It indicates the possibilities of better utilization of wood wastes.